2007
DOI: 10.1124/jpet.107.122705
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Adenosine Effects and Adenosine Receptors in Murine Corpus Cavernosum

Abstract: This study tested the hypothesis that adenosine, in murine corpora cavernosa, produces direct relaxation of smooth muscle cells and inhibition of contractile responses mediated by sympathetic nerve stimulation. Penes were excised from anesthetized male C57BL/6 mice, dissected, and cavernosal strips were mounted to record isometric force. Adenosine, 2-chloroadenosine (stable analog of adenosine), and 2-phenylaminoadenosine (CV1808) (A2 A /A2 B agonist) produced concentrationdependent relaxations of phenylephrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 37 publications
6
42
1
3
Order By: Relevance
“…Experiments on isolated rabbit corpus cavernosum suggested that A 2B receptors were also involved in relaxation [189]. In another paper, it was claimed that adenosine directly relaxes cavernosal smooth muscle via both A 2A and A 2B receptor subtypes, while it modulates sympathetic neurotransmission via A 1 receptors [404]. Activation of A 1 receptors during penile erection results in reduced noradrenaline (NA) release and reduced cavernosal smooth muscle contraction, thereby facilitating penile erection [303].…”
Section: Penis and Penile Erectionmentioning
confidence: 99%
“…Experiments on isolated rabbit corpus cavernosum suggested that A 2B receptors were also involved in relaxation [189]. In another paper, it was claimed that adenosine directly relaxes cavernosal smooth muscle via both A 2A and A 2B receptor subtypes, while it modulates sympathetic neurotransmission via A 1 receptors [404]. Activation of A 1 receptors during penile erection results in reduced noradrenaline (NA) release and reduced cavernosal smooth muscle contraction, thereby facilitating penile erection [303].…”
Section: Penis and Penile Erectionmentioning
confidence: 99%
“…Those factors, which regulate contraction and relaxation of vascular smooth muscle, determine the state of the penis (flaccidity versus erection) (Andersson, 2001;Tostes et al, 2007;Nunes et al, 2012). The flaccid state is mainly mediated by the release of norepinephrine from adrenergic nerve terminals and other vasoconstrictors, such as endothelin-1 and angiotensin II (Sáenz de Tejada et al, 1989, 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The flaccid state is mainly mediated by the release of norepinephrine from adrenergic nerve terminals and other vasoconstrictors, such as endothelin-1 and angiotensin II (Sáenz de Tejada et al, 1989, 2004. The erection is mainly mediated by nitric oxide (NO) released from the endothelium and nonadrenergic-noncholinergic nerves in addition to other neurotransmitters and endothelium-derived hyperpolarizing factors (EDHFs), such as adenosine (Chiang et al, 1994;Tostes et al, 2007;Wen et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Tostes et al (2007) presented data suggesting that adenosine-induced relaxation in mouse CC is mediated through activation of both A 2A and A 2B adenosine receptors. Mice lacking adenosine deaminase (which is necessary for the breakdown of adenosine) showed priapic activity involving A 2B receptors (Mi et al, 2008).…”
Section: Erectile Mechanisms and Ed Treatmentmentioning
confidence: 99%